Liver function parameters, cholesterol, and phospholipid α-linoleic acid are associated with adipokine levels in overweight and obese adults - Gray, Belinda; Steyn, Frederik; Davies, Peter Stephen Wynford; Vitetta, Luis (Nutrition research (New York, N.Y.), 2014)
Dysregulation of adipose hormones in obesity has been associated with the hastened development of metabolic syndrome and associated chronic disease sequalae including cardiovascular disease and type 2 diabetes mellitus. This study aims to identify common biochemical and anthropometric markers that impact adipose hormones, including adiponectin and leptin. Based on previous literature, it was hypothesized that these would be adversely impacted by liver function parameters, and adiponectin levels would be positively correlated with phospholipid Ω-3 fatty acids. Forty nondiabetic adult subjects (body mass index, ≥25.0 kg/m2) were recruited. Fasting plasma samples were taken to assess adipokine levels, glucose metabolism, electrolytes, liver enzymes, and blood lipids. Basic anthropometric measurements were also recorded. Adiponectin levels were positively correlated with high-density lipoprotein cholesterol and negatively correlated with anthropometric measures, insulin, liver enzymes, triglycerides, and very low–density lipoprotein cholesterol but not body mass index. Conversely, plasma leptin levels were positively correlated with anthropometric measures, C-reactive protein, high-density lipoprotein cholesterol, and plasma phospholipid proportions of Ω-3 α linoleic acid but inversely correlated with creatinine levels. These results support other data regarding correlations between adiponectin and relative adipose distribution. Correlations with specific liver enzymes may indicate that adiponectin levels are tied to fatty acid deposition in the liver; however, liver/kidney damage though further mechanistic clarification is required. Leptin levels were associated with measures of adiposity but not liver enzymes. Each of these variables, along with blood lipids, may serve as potential future therapeutic targets for the prevention and management of obesity and related comorbidities.